First record of Chromodoris annulataEliot, 1904 (Mollusca:Chromodorididae) in the Syrian marine waters - حسن محمد; علي عبداللطيف; الشيخ احمد علاء (Latakia University Journal -Biological Sciences Series, 2020)
Chromodorisa nnulata Eliot, 1904 is an Opisthobranch species indigenous to the Indian Ocean, and is common along the eastern African coast and the Red Sea. In the present paper, the first record of Chromodoris annulata (Mollusca: Chromodorididae) from the Mediterranean coasts of Syria is reported.The specimen was photographed and caught on shallow rocky habitat in the Syrian marine waters (Tartous) during a permanent ichthyologic survey on 7th February 2020.